A novel design-based optimization framework for enhancing the energy efficiency of high-rise office buildings in urban areas. (August 2019) - Javanroodi, Kavan; Nik, Vahid M.; Mahdavinejad, Mohammadjavad
Highlights: A multi-objective optimization framework to find optimal forms in urban areas. With a novel design-based approach emphasizing on geometry and energy calculations. 1998 optimal form combinations generated and studied considering urban microclimate. 34% energy demand and 12% thermal discomfort reduction adopting the framework. A series of design-based recommendations presented for early-design stage. Abstract: Designing high-rise buildings is a complex and challenging task involving several parameters and variables. Recently, there have been major attempts to design the overall form of these buildings based on optimization approaches. This paper introduces a multi-objective optimization framework based on Genetic Algorithm, namely Energy Efficient Form-finder (EEF), consisting four main steps of Form-Generation, Form-Simulation, Form-Optimization and Form-Solutions. The EEF with a comprehensive design-based approach is evaluated through five functions considering objectives of minimizing cooling and heating demand and thermal discomfort time while maintaining operative temperature on the defined thermal comfort zone. This work studies the form combination of five reference buildings based on a new technique called "Building Modular Cell" in five different urban areas, resulting in twenty-five distinct design problems. According to the results, there is a great potential to adopt EEF in newly-built projects with a rectangular layout; while it can reduce the annual energy demand and thermal discomfort time of the optimal form combinations around 34% and 12% respectively. Finally, a series of qualitative and quantitative design-aid recommendations are presented based on 1998 best design solutions, which can be used as form-finding rules of thumb by architects and urban designers at the early design stages.